PEMENUHAN HAK TERDAKWA DALAM PELAKSANAAN PERSIDANGAN ONLINE DI MASA PANDEMI COVID-19: Fulfilling The Defendant's Rights In Conducting Online Trials During The Covid-19 Pandemic - Nadilatunnisa, Nida; Hadjar, Abdul Ficar (AMICUS CURIAE, 2024)
During the Covid-19 pandemic, many activities had to be carried out online, such as learning at schools and universities. This also has an impact on the trial process which cannot be carried out in person but by means of electronic (online) criminal case trials. In the trial process at the Serang District Court, there was an irregularity in the proceedings. Where the defendants were not physically present during the trial at the Serang District Court, while the panel of judges, prosecutors and witnesses were. presented, with the witness a member of the police. Here the witness, namely a member of the police, plays the role of arresting the defendant. Therefore, based on the background explained by the author above, the author is interested in conducting further research regarding the problems that occur in the trial process, namely how the defendant's rights can be fulfilled in carrying out online trials during the Covid-19 pandemic. In this research, the type of research used is empirical juridical research. The results of this research are that the defendant's rights during the online trial are still fulfilled, and run according to the Criminal Procedure Code. Therefore, it can be concluded that the defendant's rights in the online trial process are still fulfilled. Because online trials are still carried out based on the Criminal Procedure Code and PERMA No. 4 of 2020.